Effect of filler dispersion on the electromechanical response of epoxy/vapour grown carbon nanofiber composites - Ferreira, A. (2012)
The piezoresistive response of epoxy/vapour grown carbon nanofiber composites prepared by four different dispersion methods achieving different dispersion levels has been investigated. The composite response was measured as a function of carbon nanofiber loading for the different dispersion methods. Strain sensing by variation of the electrical resistance was tested through 4-point bending experiments, and the dependence of the gauge factor as a function of the deformation and velocity of deformation was calculated as well as the stability of the electrical response. The composites demonstrated an appropriate response for being used as a piezoresistive sensor. Specific findings were that the intrinsic piezoresistive response was only effective around the percolation threshold and that good cluster dispersion was more appropriate for a good piezoresistive response than a uniform dispersion of individual nanofibers. The applications limits of these materials for sensors applications are also addressed.